A bibliometric and content analysis of core researches on operations research. (2nd March 2023) - Modak, Nikunja Mohan; Raj, Alok; Sana, Shib Sankar
Operations research emerged as a discipline after the Second World War due to its efficiency to make better decisions. The socio-economic environment world over has changed over the last 50 years, and operations research has played a vital role in complex decision making. Advanced analytical methods of operations research are effective for improving decision making and solving real life problems in business, industry, and society. This work presents a bibliometric and content analysis of core publications of operations research. This study exclusively considers publications with operations research in their title. We have used SCOPUS, a reliable database, to collect relevant data. It presents overall publications and structure of citations. It comprehensively studies the significant contributions of journals, universities, and countries on this topic. Using the visualisation of similarities viewer software, it presents network visualisations and analyses co-occurrence of keywords, co-citations, and bibliographic coupling of institutions and countries. Finally, the paper reviews highly influential articles in this field and provides comprehensive direction for future research in this field.